2021
DOI: 10.2169/internalmedicine.5564-20
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis Intestinalis in Lung Cancer Induced Twice by Different Drugs: Bevacizumab and Pemetrexed

Abstract: A 72-year-old man diagnosed with stage 4 lung adenocarcinoma developed asymptomatic pneumatosis intestinalis while undergoing treatment with first-line chemotherapy, which included carboplatin, paclitaxel, and bevacizumab (BEV). He was treated conservatively. The pneumatosis recurred while the patient was undergoing treatment with the third-line chemotherapy, which included pemetrexed (PEM). His condition resolved after 4 weeks of supportive therapy. To our knowledge, this is the first case in which pneumatosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…All titles were screened, after which 65 full-text articles were assessed for eligibility. Ultimately, 50 records that met our eligibility criteria were identified, and 12 more reports were retrieved through reference mining, reaching a total of 62 articles that were included in our systematic review ( Figure 2 ) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 62 , 64 , 65 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All titles were screened, after which 65 full-text articles were assessed for eligibility. Ultimately, 50 records that met our eligibility criteria were identified, and 12 more reports were retrieved through reference mining, reaching a total of 62 articles that were included in our systematic review ( Figure 2 ) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 62 , 64 , 65 , 67 , 68 , 69 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Among adult patients, secondary PI is mainly associated with gastrointestinal disease, pulmonary diseases, mechanical ventilation, endoscopic procedures, infections and other immunological conditions [ 8 ]. Medications used for cancer treatment are among the most recognized causes of PI, including cytotoxic chemotherapeutic agents [ 9 ] and molecular targeted agents [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Six studies on steroid-related PI ( Galm et al, 2001 ; Han et al, 2002 ; Patel et al, 2014 ; Ozturk et al, 2017 ; Lee and Wu, 2019 ; Nunomiya et al, 2021 ) were included. Patient characteristics, medication therapies, treatments, prognosis, and outcomes are summarized in Table 1 .…”
Section: Literature Review Of Steroid-related Pi Casesmentioning
confidence: 99%
“…Patient characteristics, medication therapies, treatments, prognosis, and outcomes are summarized in Table 1 . Eight cases of PI secondary to the combined therapy of steroids and other cytotoxic, immunosuppressive agents ( Galm et al, 2001 ; Patel et al, 2014 ; Ozturk et al, 2017 ; Nunomiya et al, 2021 ) were identified, and two cases of PI secondary to steroid monotherapy ( Han et al, 2002 ; Lee and Wu, 2019 ). In addition, six patients had underlying hematopoietic and lymphoid system conditions ( Galm et al, 2001 ; Patel et al, 2014 ); one patient had lung adenocarcinoma, another had nasopharyngeal cancer ( Ozturk et al, 2017 ; Nunomiya et al, 2021 ), and the remaining two had nephrotic syndromes ( Han et al, 2002 ) and superior mesenteric artery syndromes ( Lee and Wu, 2019 ).…”
Section: Literature Review Of Steroid-related Pi Casesmentioning
confidence: 99%
See 1 more Smart Citation